PERBANDINGAN POTENSI ANALGETIK EKSTRAK ETANOL DAN AIR UMBI RUMPUT TEKI (Cyperus rotundus L.) TERHADAP TIKUS Sprague Dawley - Erni Rustiani; Min Rahminiwati; Tia Mutiara (Universitas Pakuan, 2017)
The aim of this study is to compare the potential of ethanolic and water extracted of teki grasstuber on white male rat strain Sprague Dawley at two months of age and 200 g of body weight. The rats were divided among four groups. Each group consists of six rats. The groupswere ethanolic and water extracted of teki grass tuber, positive control group (Paracetamol) and a negative control group (distilled water). Analgesic potency was tested by inducing pain stimuli previously to the animals, in the form of heat stimuli by putting it ona hot plate with the temperature of 55C. The responses of rats observed were licking and moving or lifting of their legs. Observations were made for 1 minute, before and after administration of pain stimulus at 15, 30, 45 and 60 minute. The results showed that ethanol and water extract at an effective dose of 49 mg / 200 g of BW, gave relatively the same effect as an analgesic or positive control group.Keywords : analgesic, ethanol and water extract of teki grass tuber, pain